Elderly case and assistance booking platform - Hew, Zi Xuan (2024)
The Elderly Care and Assistance Booking Platform project aims to address the urgent need in Malaysia for an interactive platform that enables customers to access care services and facilitates direct interaction with caregivers. Currently, there is a large gap in such platforms, making this project highly relevant and impactful. The project focuses on developing a platform that enables registration, strong communication channels, and comprehensive search capabilities for customized care services for clients and caregivers. The project adopts a Rapid Application Development (RAD) approach to ensure agility and adaptability to meet the changing needs of the care sector. This approach helps to quickly adjust and respond to user preferences and emerging needs. By leveraging insights gained from the existing platform, the project aims to enhance the well-being of clients and caregivers throughout Malaysia. To ensure the platform meets the highest standards of quality and functionality, four types of testing will be conducted. The testing includes unit testing, feature testing, black-box testing, and user acceptance testing (UAT). These tests will cover various aspects of the platform from individual components to the overall user experience. An attractive feature of the platform is its AI recommendation system. This system is designed to personalize care service suggestions based on user preferences and needs. This system provides tailored recommendations and enhances the matching process between clients and caregivers. Additionally, the platform includes a GPT-powered description function that generates detailed and context-aware descriptions of services. This further improves the user experience and facilitates informed decision-making. For this project, Laravel serves as the project's fundamental framework. Laravel ensures safe data management, user authentication, and scalability via its Model-View Controller (MVC) architecture. This strong architecture facilitates the platform's expansion and adaptability which gives a safe and scalable response to the changing needs of elderly care service.